Behavioral and Brain Functions - Crusio, Wim
A well-established journal in the field of behavioural and cognitive neuroscience, Behavioral and Brain Functions welcomes manuscripts which provide insight into the neurobiological mechanisms underlying behaviour and brain function, or dysfunction. The journal gives priority to manuscripts that combine both neurobiology and behaviour in a non-clinical manner.